Keadilan Ekonomi Islam dan Implementasinya - Ahmad Ubaidillah; Khozainul Ulum (Universitas Islam Lamongan, 2023)
This paper attempts to answer two questions: what is justice in Islamic economics and what is the manifestation of justice in Islamic economics. This research is library research, by using a qualitative approach which produces descriptive data in the form of written words. The data analysis technique used in this research is hermeneutics. The research results show: First, Islamic economics is based on the idea of distributive justice. The concept of justice in the Islamic economic system is distributive justice, namely treatment of someone according to the services they have performed. With distributive economic justice, everyone will get their rights according to the contribution they make, and at the same time everyone must also be free from exploitation of other people. In other words, Islamic economic justice requires a state of 'neither tyrannizing nor being wronged'. Second, the philosophical value of Islamic economic justice can be applied to various economic activities: products, distribution, consumption, finance, business, development, and so on. The practice of justice in Islamic economics can also be found in the rationality of profit and loss sharing (PLS). One of the characteristics of the Islamic economic system is the distribution of profit and loss. Stakeholders share profit and loss using a PLS system. Muá¸arabah and musyarakah are two instruments of distribution in economic activities that provide justice.